Psikologi Qurani dalam Dakwah: Telaah Kritis Psikologi Dalam Perspektif Al-Qur’an - Tanuri (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2023)
Al-Quran is the word of Allah from the sky which must be grounded as a guide from Allah to His servants. Al-Qur'an which contains text makes some of its readers refer to the text and meaning literally and without including asbabun nuzul or the reasons for the revelation of a verse or al-Qur'anic text in their interpretation. Outside the text there are events that cause the revelation of a verse or asbabun nuzul. Some classical scholars place more emphasis on textual interpretations while contemporary scholars see the need to combine asbabun nuzul and contexts which are relatively abreast of the times. Some other groups see the need for contestual development to give birth to new ideas related to muamalah and law. A separate problem is combining textual and contextual with asbabun nuzul references. This study uses the literature review method, namely research carried out using literature in the form of books, notes and reports on the results of previous research, by reading, studying and recording various literature or reading materials that are in accordance with the subject matter, then filtered and outlined in a theoretical frame of mind . And the results of this study are that maqashidu sharia or the aim of sharia is to be a solution or middle ground for the problems above. It becomes glue for textual verses that have different contexts, in order to answer problems in a dynamically changing society.